2016
DOI: 10.1111/desc.12488
|View full text |Cite
|
Sign up to set email alerts
|

Post‐conflict slowing effects in monolingual and bilingual children

Abstract: Previous research has shown that bilingual children outperform their monolingual peers on a wide variety of tasks measuring executive functions (EF). However, recent failures to replicate this finding have cast doubt on the idea that the bilingual experience leads to domain-general cognitive benefits. The present study explored the role of disengagement of attention as an explanation for why some studies fail to produce this result. Eighty children (40 monolingual, 40 bilingual) who were 7 years old performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Given that greater brain signal complexity is believed to index the ability to rapidly switch brain states (Deco, Jirsa, & McIntosh, 2011; Beharelle Kovačević, McIntosh, & Levine, 2012), these findings suggest a greater ability for bilinguals to switch brain states in occipital (i.e., possibly visual) regions than monolinguals. Recent evidence from our lab suggests that bilinguals are able to disengage attention from visually presented items more rapidly than monolinguals (Grundy et al, 2017, Grundy & Keyvani-Chahi, 2017), a process that requires more advanced visual processing. In these experiments, the items are visually simple like the stimuli used here.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Given that greater brain signal complexity is believed to index the ability to rapidly switch brain states (Deco, Jirsa, & McIntosh, 2011; Beharelle Kovačević, McIntosh, & Levine, 2012), these findings suggest a greater ability for bilinguals to switch brain states in occipital (i.e., possibly visual) regions than monolinguals. Recent evidence from our lab suggests that bilinguals are able to disengage attention from visually presented items more rapidly than monolinguals (Grundy et al, 2017, Grundy & Keyvani-Chahi, 2017), a process that requires more advanced visual processing. In these experiments, the items are visually simple like the stimuli used here.…”
Section: Discussionmentioning
confidence: 91%
“…After obtaining informed consent, participants completed the three background measures followed by the bivalency effect task (2013, Grundy & Shedden, 2014a, 2014b; Grundy & Keyvani Chahi, 2017; Meier, Woodward, Rey-Mermet, & Graf, 2009; Woodward, Meier, Tipper, & Graf, 2003) while simultaneous EEG was recorded. The experiment lasted approximately 90 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…However, the focus of recent research has shifted to switching, monitoring, disengagement of inhibition, refocusing of attention, or post-conflict effects as possible areas where the impacts of bilingualism can be detected (Prior & MacWhinney, 2010;Costa, Hernández, Costa-Faidella & Sebastián-Gallés, 2009;Treccani, Argyri, Sorace & Della Sala 2009;Grundy & Chahi 2016). The hypothesis that bilinguals have better switching abilities assumes that bilingual speakers develop an enhanced ability to shift and refocus attention from task to task, and to and from different mental sets, as a result 6 of their daily experience in switching from one language to another.…”
Section: Bilingual Language Processing and Cognitionmentioning
confidence: 99%
“…There is some existing evidence that bilinguals disengage from previous distracting information more rapidly than monolinguals (Grundy & Keyvani Chahi, 2017; Mishra, Hilchey, Singh, & Klein, 2012). Task-switching studies that examine the cost of switching from one task to another versus repeating the same task have shown that bilinguals show smaller switch costs than monolinguals (Prior & Gollan, 2011; Prior & MacWhinney, 2010).…”
Section: Introductionmentioning
confidence: 99%